The burden of prosthetic hip dislocations in the United States is projected to significantly increase by 2035. Issue 6 (November 2021) - Pirruccio, Kevin; Premkumar, Ajay; Sheth, Neil P
Introduction: Prosthetic hip dislocation is a common, costly complication of total hip arthroplasty (THA). Despite this, the national burden of prosthetic hip dislocations remains uncharacterised in the United States, especially pertaining to injuries occurring years after the index procedure. This study examines historical and projected national estimates of prosthetic hip dislocations presenting to U.S. emergency departments between 2000 and 2035. Methods: We conducted a cross-sectional, retrospective epidemiological study using narratives in the National Electronic Injury Surveillance System (NEISS) database (2000–2017) to identify an estimated 64, 671 prosthetic hip implant dislocations presenting to U.S. emergency departments. Estimates for the prevalence of individuals living with a total hip implant were derived from the literature. Results: The national estimate of prosthetic hip dislocations presenting to U.S. emergency departments rose significantly ( p < 0.001) between 2000 ( n = 2395; 95% CI, 1264–3526) and 2017 ( n = 8094; 95% CI, 4276–11, 912). These increases are likely driven by increased numbers of people living with THA overall, since between 2000 and 2017, the average incidence of prosthetic hip dislocation (0.14%; CI 0.08–0.21%) in patients living with hip implants has not changed significantly. Linear regression modeling (R 2 = 0.7, p < 0.01) projected an increasing number of dislocations through 2035, predicting 10, 446 national cases per year by this date. Conclusions: Driven by increases in THA, the annual volume of prosthetic hip dislocations presenting to U.S. emergency departments has increased significantly since 2000 and is projected to continue to rise sharply. Future advances in surgical technique, prosthesis design, and injury prevention policies aimed at decreasing the rate of THA dislocation would help alleviate this mounting national health burden.